Comparing multiple sampling platforms for measuring the behavior of humpback whales (Megaptera novaeangliae). Issue 1 (14th September 2015) - Godwin, Elise M.; Noad, Michael J.; Kniest, Eric; Dunlop, Rebecca A.
Abstract: Multiple platform approaches for measuring the behavior of marine mammals may strengthen data quality and quantity. However, if this approach is chosen, reconciliation of behavioral measures between each platform is required. This study compared typical measures of humpback whale ( Megaptera novaeangliae ) behavior collected from three different sampling platforms; land‐based, boat‐based, and digital tags (Dtags), to explore similarities and/or discrepancies in data. Visual observations from land‐based platforms significantly underestimated group blow rate when compared to boat‐based platforms, whereas broad‐scale spatial movements (speed and course traveled) were measured similarly by these two platforms. Dtags were used to define dive behavior based on a time and depth criteria, where bouts of short shallow respiration dives (≤80 s and ≤10 m) were separated from longer, deeper dives (>80 s and >10 m). At a group level, land and boat platforms agreed on the number of long dives but land platforms missed bouts of short dives. At an individual level, the number of short and long dives observed by boat‐based platforms agreed with Dtag recordings. This study highlights the importance of data exploration prior to analyses in multiple platform studies to identify potential discrepancies and appropriately account for any biases.